Do cases like that of Anders Breivik show that fanaticism is a form of madness? Yes. (11th July 2012) - Taylor, Max
Abstract : The trial of Anders Breivik, who murdered 77 people in two attacks in Norway, has attracted considerable controversy because of the questions concerning his mental state. Max Taylor argues that such extreme fanatics should be considered insane, but Tom Fahy (doi:10.1136/bmj.e4647 ) believes that a psychiatric diagnosis is an abrogation of personal and societal responsibility